Biotopic distribution of small mouse-like rodents in the Caspian-sandy natural plague center - E. V. Gerasimenko; A. Y. Gazieva; A. K. Khalidov; A. A. Kesyan (Наука. Инновации. Технологии)
Introduction. The territory of the Caspian sandy hearth (43) occupies the eastern part of the Northwestern Caspian Sea, starting from the lower reaches of the Volga in the northeast to the lower reaches of the Terek in the south, the eastern boundary of the hearth is the coastline of the Caspian Sea. In landscape terms, the territory is a slightly hilly, almost flat plain inclined towards the sea.Materials and methods of research. The work is based on the analysis of the results of long-term epizootological monitoring for the period 2010–2020, conducted in the Caspian sandy plague outbreak by specialists of the Kizlyar and Budyonnovsky anti-plague department of the Dagestan AntiPlague Station of Rospotrebnadzor.Results. The ecosystems of the LEHR “Kizlyar Steppe” and “Nogai Steppe” differ both in the number of species of small mouse-like rodents and in their association with biotopes. The fauna of mouse-like rodents in the LEHR “Kizlyar Steppe” is eurytopic, the LEHR “Nogai Steppe” is represented by six species of which only two are eurytopic: the public vole and the house mouse. The fauna of mouse-like rodents is common in the landscape and climatic regions of the “Nogai and Mozdok steppe of the UK”, most species are eurytopian, although each species has its own favorite biotope, with a more pronounced confinement.Conclusions. These calculations will optimize the work of epizootological examination of the territory of the Caspian sandy hearth.